Population biology of the sea star Anasterias minuta (Forcipulatida: Asteriidae) threatened by anthropogenic activities in rocky intertidal shores of San Matías Gulf, Patagonia, Argentina - Arribas, Lorena P.; Bagur, María; Palomo, M. Gabriela; Bigatti, Gregorio (Revista de Biología Tropical, 2017)
In Patagonian coastal areas, intertidal benthic communities are exposed to extreme physical conditions. The interaction between harsh environment and anthropogenic pressure can generate changes in population biology of marine invertebrates, like density and reproduction. The oral brooding sea star Anasterias minuta is a key organism in food chains of Atlantic Patagonian rocky intertidals, hence changes on its population structure can negatively affect shore communities. We studied the population biology of A. minuta and assess the effect of environmental parameters and anthropogenic activities on its population on rocky intertidal shores of San Matías Gulf, Patagonia, Argentina. Seasonal sea surface temperature, pH, salinity, water velocity, desiccation rate, boulders density, and anthropogenic influence (tourists and octopus fishermen) were recorded. In sites with less tourist influence and high refuge, an increase in density was recorded, especially during the summer. Brooding individuals were found in fall and winter, while feeding individuals were observed in all seasons (12 different prey, mainly the molluscs Tegula patagonica and Perumytilus purpuratus). Environmental variables such as boulders density and water velocity were the most important predictor of variation in population structure. Tourism and pH were the most important variables negatively correlated with density. Rev. Biol. Trop. 65(Suppl. 1): S73-S84. Epub 2017 November 01.